Aspectos biológicos e toxicidade de produtos de origem vegetal a Euborellia annulipes - Silva, Aldeni Barbosa da (2009)
Among the methods of controlling insect pests, the use of pesticides has been reduced in negative consequences on the beneficial fauna and the environment, so it is therefore necessary to search for alternatives that minimize the adverse effects of pesticides on the environment. As alternatives to control pests, are being studied, several other techniques, which includes the use of origin plant substances because they have low toxicity to humans and animals, and for presenting performance against several species of pests, which assumes increasing importance in programs of integrated pest management (MIP), especially at a time when it discusses very integrated production towards sustainable agriculture. The insects belonging to the order Dermaptera, are still not well known and the information in the literature, characterized as predatory bodies with good ability. Among the biological agents with characteristics suitable for this purpose, the dermápteros have attracted great attention because predators are greedy, that is, with high ability to attack and feeding on different prey, particularly of eggs and immature stages insects of the orders Lepidoptera, Hemiptera, Coleoptera and Diptera. Considering the potential use of preying on programs for biological control, studies related to their biology and their selectivity in plant extracts become indispensable. Thus, the aim of this work was to study the biological aspects of Euborellia annulipes fed on Spodoptera frugiperda and Hyadaphis foeniculi and selectivity of this predator to products of plant origin in laboratory conditions.